Solution of the space-fractional telegraph equations by using HAM - Abedi-Varaki, Mehdi; Rajabi, Shahram; Ghorbani, Vahid; Hosseinzadeh, Farzad (Ciência e Natura, 2015)
In this study by using the Homotopy Analysis Method (HAM) obtained approximate solutions for the space and time-fractional telegraph equations. In Caputo sense (Yildirim, 2010)these equations considered. Examples are solved and the obtained results show to be more accurate than Adomian Decomposition Method (ADM) and are more efficient and commodious.